Effect of Autophagy Inhibition on the Protection of Ischemia Preconditioning against Myocardial Ischemia/Reperfusion Injury in Diabetic Rats - Ya-Yang Liu; Chao Sun; Fu-Shan Xue; Gui-Zhen Yang; Hui-Xian Li; Qing Liu; Xu Liao (Chinese Medical Journal, 2018)
Background: Ischemia preconditioning (IPC) remains the most powerful intervention of protection against myocardial ischemia/reperfusion injury (IRI), but diabetes can weaken or eliminate its cardioprotective effect and detailed mechanisms remain unclear. In this study, we aimed to explore whether changes of autophagy in the diabetic condition are attributable to the decreased cardioprotective effect of IPC. Methods: Sixty diabetic male Sprague-Dawley rats were randomly divided into the control (C), IRI, rapamycin (R), wortmannin (W), rapamycin + IPC (R + IPC), and wortmannin + IPC (W + IPC) groups. The in vivo rat model of myocardial IRI was established by ligaturing and opening the left anterior descending coronary artery via the left thoracotomy. Durations of ischemia and reperfusion are 30 min and 120 min, respectively. Blood samples were taken at 120 min of reperfusion for measuring serum concentrations of troponin I (TnI) and creatine kinase isoenzyme MB (CK-MB) using the enzyme-linked immunosorbent assay. The infarct size was assessed by Evans blue and triphenyltetrazolium chloride staining. The expressions of LC3-II, beclin-1, phosphoinositide 3-kinase (PI3K), mammalian target of rapamycin (mTOR), and P-Akt/Akt ratio in the ischemic myocardium were assessed by Western blotting. Results: Compared to the IRI group, infarct size (56.1% ± 6.1% vs. 75.4 ± 7.1%, P < 0.05), serum cTnI (0.61 ± 0.21 vs. 0.95 ± 0.26 ng/ml, P < 0.05), and CK-MB levels (6.70 ± 1.25 vs. 11.51 ± 2.35 ng/ml, P < 0.05) obviously decreased in the W + IPC group. Compared with the C group, myocardial expressions of LC3-II (0.46 ± 0.04 and 0.56 ± 0.04 vs. 0.36 ± 0.04, P < 0.05) and beclin-1 (0.34 ± 0.08 and 0.38 ± 0.07 vs. 0.24 ± 0.03, P < 0.05) evidently increased, and myocardial expressions of mTOR (0.26 ± 0.08 and 0.25 ± 0.07 vs. 0.38 ± 0.06, P < 0.05), PI3K (0.29 ± 0.04 and 0.30 ± 0.03 vs. 0.38 ± 0.02, P < 0.05), and P-Akt/Akt ratio (0.49 ± 0.10 and 0.48 ± 0.06 vs. 0.72 ± 0.07, P < 0.05) markedly decreased in the IRI and R groups, indicating an increased autophagy. Compared with the IRI group, myocardial expression of beclin-1 (0.26 ± 0.03 vs. 0.34 ± 0.08, P < 0.05) significantly decreased, and myocardial expressions of mTOR (0.36 ± 0.04 vs. 0.26 ± 0.08, P < 0.05), PI3K (0.37 ± 0.03 vs. 0.29 ± 0.04, P < 0.05), and P-Akt/Akt ratio (0.68 ± 0.05 vs. 0.49 ± 0.10, P < 0.05) increased obviously in the W + IPC group, indicating a decreased autophagy. Conclusions: Increased autophagy in the diabetic myocardium is attributable to decreased cardioprotection of IPC, and autophagy inhibited by activating the PI3K-Akt-mTOR signaling pathway can result in an improved protection of IPC against diabetic myocardial IRI.